Paradox of openness: knowledge sharing-protection tension in ecosystems - Paasi, Jaakko; Valkokari, Katri; Rusanen, Helena; Makkonen, Hannu; Laiho, Tiina (Lappeenranta-Lahti University of Technology LUT, 2020)
The paper describes findings about knowledge management in innovation constellations that are calling themselves as innovation ecosystems. The focus is in tension between knowledge sharing and knowledge protection, i.e. in the paradox of openness. The research asked whether an ecosystemic and open way of innovation differs to innovation in networks in respect to how the paradox appears. The study applied the methodology of qualitative research. Experiences and practices were collected from 13 innovation ecosystems. According to the findings, the paradox seems to be very true in ecosystems and even more pronounced than in innovation networks, because in ecosystems one may not know all actors of innovation. That makes the promotion of knowledge sharing in ecosystems as a multifaceted issue. In addition, the findings suggest that firms in different ecosystem roles have role specific approaches towards sharing vs. protection.
Keywords: industry 4.0.; innovation ecosystems; innovation networks; intellectual property; knowledge protection; knowledge sharing; open innovation; paradox of openness; knowledge management; ecosystems; fi=Markkinointi|en=Marketing|